EDUKASI MANAJEMEN KEUANGAN MELALUI APLIKASI DIGITAL DALAM UPAYA PENINGKATAN LITERASI DI KALANGAN PELAJAR - fadhly; Ansari, Ansari (Forum Komunikasi Dosen, 2024)
This Community Service (PKM) aims to improve financial literacy among high school students in Aceh through financial management education using digital applications. Financial literacy is crucial for young people to help them manage money wisely, especially in the digital era. The program was held on September 9, 2024, involving 50 students who participated in training sessions covering financial literacy materials, digital financial application simulations, and group discussions. The implementation method includes preparation, interactive execution, and evaluation, interspersed with ice-breaking activities throughout the program to create a fun learning atmosphere, boost motivation, and encourage active participation from the participants. The results showed high enthusiasm among participants, evident from their early attendance, active engagement, and success in group simulations. This program effectively enhanced students' understanding and motivation in financial management. This approach is expected to serve as a solution for expanding financial literacy education among students.